Meningkatkan Karakter Religius Melalui Metode Bercerita Menggunakan Media Finger Puppet (Boneka Jari) Untuk Anak Usia Dini 4 – 5 di Paud Nurul Abror Kabupaten Cianjur - Purwanti, Erni; Ashshidiqi Poppyariyana, Alfian; Zultiar, Indra (PT. Alahyan Publisher Sukabumi, 2025)
Education is the process of changing the behavior of students so that they become independent adults and participate in society. Although the primary responsibility of parents is to educate their children, teachers should be responsible for providing all preschool education to children while they are in school. Teachers are people who are directly involved in preparing the next generation to face the challenges of the times, and their role is very important in the world of education. One of the ways teachers instill character in early childhood is through stories. In teaching students, a storytelling approach is used. 1. To gain an understanding of how the role of teachers in improving religious character in PAUD Nurul Abor, Cianjur Regency.